Assessment of Hepatic Impairment and Implications for Pharmacokinetics of Substance Use Treatment. Issue 2 (March 2017) - Talal, Andrew H.; Venuto, Charles S.; Younis, Islam
Abstract: Although the liver is the primary site of metabolism and biliary excretion for many medications, data are limited on the liver's pharmacokinetic abilities in cirrhosis. Cirrhosis develops through collagen deposition, eventually culminating in end‐stage liver disease that compromises hepatic drug metabolism. Consequently, the US Food and Drug Administration (FDA) recommends evaluating the pharmacokinetics of medications in subjects with hepatic impairment if hepatic metabolism constitutes more than 20% of their elimination or if they have a narrow therapeutic range. A variety of noninvasive indices and radiologic procedures can be employed to assess hepatic drug metabolism and excretion. The Child‐Pugh score is the most commonly used scale for assessing hepatic impairment among drugs submitted for US FDA approval. The score, originally developed to guide operative mortality in patients undergoing hepatic resection, has not been modified since its inception 5 decades ago. Furthermore, the score was not originally intended to be a guide for potential dose modification in patients with hepatic impairment. These reasons, in combination with the availability of a variety of new imaging modalities and an enhanced understanding of hepatic biology, should foster the development of novel methods to assess the effect of hepatic impairment on liver drug metabolism.